La mitigación de daños en la responsabilidad por incumplimiento contractual: breve análisis comparado en el derecho civil de Argentina y Perú - Ugarte Mostajo, Daniel (2018)
The civil codes of Argentina and Perú are two of the few South American civil laws that, with different legal formulas, recognize on the creditor party a burden or duty of mitigate damages. On this basis, this paper aims to arrive, after a general approach to the duty or burden of mitigate damages in case of breach of contract, to a brief comparative analysis about the regulation that this figure has received in both civil codes, dealing with matters related not only to the structure and content of rules concerning this duty, but also to the juridical nature and foundations of the mitigation. All in order to stablish the existing similarities and differences between rules that incorporate the duty to mitigate damages in the civil codes of Argentina and Perú, the possibility of finding a common juridical foundation to both legislations, and the incidence of such a foundation in the interpretative scope of the rules mentioned.